PENGARUH MODEL TGT BERBANTUAN DAKOTA TERHADAP MINAT DAN HASIL BELAJAR MATEMATIKA KELAS V SDN JATISARI - Farikah, Fadia Nur; Sukasih, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of the times has influenced education in Indonesia to become more advanced, but the education system in Indonesia has not fully run well. Many challenges are still experienced by educators in Indonesia, especially in the context of learning Mathematics in Elementary Schools. Being one of the subjects that students are less interested in, an educator must be able to make students active and develop their individual abilities in a fun way. The purpose of this research is to investigate how the TGT learning paradigm, with assistance from Dakota Media, affects students' interest in and performance in grade V mathematics in primary schools.. This kind of research uses a nonequivalent control group design and is quasi-experimental. 30 students from class VB, the experimental class, and 31 students from class VA, the control class, both attended SDN Jatisari Semarang City. Both classes had the same ability before being given treatment. The instruments used in this study were tests and interest questionnaires. Based on the results of the hypothesis testing of the effect of interest and student learning outcomes using the t-test, the significant value is obtained < 0.05 and the tcount > ttable value, Ha is accepted and Ho is rejected. So it can be concluded that there is a significant influence between the TGT model assisted by Dakota on the interest and learning outcomes of mathematics FPB and KPK material in grade V SDN Jatisari.